A new species and key to all known species of the genus Ceracris Walker, 1870 from China (Orthoptera: Acridoidea, Arcypteridae) - Cao, Cheng-Quan; Dang, Yan; Yin, Zhan (Zootaxa, 2019)
The genus Ceracris Walker, 1870 is a median genus in Arcypteridae, which contains 23 species in the world, among them 11 species distributed in China [Walker, 1870; Bolivar, 1914; Uvarov, 1931; Zheng, 1977; Liu, 1981; Zheng, 1983; Yin, 1984; Liang, 1988; Wang, 1992; Liu et Li, 1995; Ou et al, 1995; Yin et al, 1996; Zheng et Xia, 1998; Zhang et al, 2017; Feng et al, 2018; Cigliano, 2018]. A new species of the genus from Hainan, China is described in this paper. The new species i.e. Ceracris amplicornis sp. nov. is similar to Ceracris versicolor (Brunner von Wattenwyl, 1893), but differs from latter by antennae short, length of a segment in the middle 2.9 times its width; lateral carinae of pronotum not intact and indistinct in metazona; median area of tegmen without intercalary vein; bridge of epiphallus straight and tegmen of female short, reaching the end of hind femur only. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China.